2022
DOI: 10.1128/mbio.03752-21
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Indole as a Multifunctional Regulator of Klebsiella oxytoca Complex Enterotoxicity

Abstract: The human gut harbors a complex community of microbes, including several species and strains that could be commensals or pathogens depending on context. The specific environmental conditions under which a resident microbe changes its relationship with a host and adopts pathogenic behaviors, in many cases, remain poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…A report indicates that diseases caused by K. pneumoniae or K. oxytoca do not strictly coincide (10), but there have been no previous reports that indole-positive K oxytoca is more virulent. In a recent study on K. oxytoca and Klebsiella grimontii, the authors reported that bacterial indole functions as a regulator that inhibits the synthesis of bacterial toxins and mitigates tissue cytotoxicity (11). In the present study, the pathogenic changes in K. oxytoca that were indole-negative were unknown and may be clarified in the future through infection experiments using animals.…”
Section: Accepted Manuscriptmentioning
confidence: 71%
“…A report indicates that diseases caused by K. pneumoniae or K. oxytoca do not strictly coincide (10), but there have been no previous reports that indole-positive K oxytoca is more virulent. In a recent study on K. oxytoca and Klebsiella grimontii, the authors reported that bacterial indole functions as a regulator that inhibits the synthesis of bacterial toxins and mitigates tissue cytotoxicity (11). In the present study, the pathogenic changes in K. oxytoca that were indole-negative were unknown and may be clarified in the future through infection experiments using animals.…”
Section: Accepted Manuscriptmentioning
confidence: 71%
“…Following gene editing, both plasmids could be easily cured, creating markerless strains for downstream analyses. Given the increasing interest in characterizing competitive interactions between gut bacteria and Klebsiella species in particular 5,6,13,39,40 , we anticipate that our tool will contribute to mechanistic studies of microbiome communities.…”
Section: Discussionmentioning
confidence: 99%
“…Multilocus sequence type 1 was assigned ( 14 ) (isolate 34) and cytotoxicity towards cultured human cells was assessed ( 15 ) (see strain 04/1O). Murine infection models confirmed in vivo toxin production by AHC-6 ( 16 , 17 ), identified the molecular targets of tilimycin and tilivalline, providing a mechanistic link to epithelial cell damage ( 7 , 16 ), and showed that the genotoxicity induced by tilimycin generates DNA lesions in enterocytes ( 16 ) and decreases microbial diversity while promoting the emergence of antibiotic resistance in the gut microbiome ( 18 ).…”
Section: Announcementmentioning
confidence: 95%